2020
DOI: 10.1055/a-1248-2022
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Ischemic and Hemorrhagic Strokes – A Pilot Study with Transtemporal Investigation of Brain Parenchyma Elasticity Using Ultrasound Shear Wave Elastography

Abstract: Introduction Ultrasound shear wave elastography is well established in diagnostics of several parenchymatous organs and is recommended by respective guidelines. So far, research about applications in relevant neurological conditions is missing, especially in adults. Here we aimed to examine the method for the differentiation of ischemic (IS) and hemorrhagic strokes (HS) and cerebral mass effects. Materials & Methods 50 patients with a confirmed diagnosis of HS or IS were enrolled in this prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…More recently, SWE reference data have been reported for transcranial 2D-SWE of the brain in healthy adults at various ages [54]. The same group was able to show that transcranial SWE may discriminate between brain hematoma and brain infarction 1-2 days after the insult [55]. However, there is still a need of methodological standardization, and the elucidation of dynamic changes of brain elasticity [56].…”
Section: Ultrasound Imaging Modality Application In Humans (Any Clini...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, SWE reference data have been reported for transcranial 2D-SWE of the brain in healthy adults at various ages [54]. The same group was able to show that transcranial SWE may discriminate between brain hematoma and brain infarction 1-2 days after the insult [55]. However, there is still a need of methodological standardization, and the elucidation of dynamic changes of brain elasticity [56].…”
Section: Ultrasound Imaging Modality Application In Humans (Any Clini...mentioning
confidence: 99%
“…In jüngerer Zeit wurden SWE-Referenzdaten für die transkranielle 2D-SWE des Gehirns bei gesunden Erwachsenen in verschiedenen Altersgruppen veröffentlicht [54]. Dieselbe Arbeitsgruppe konnte zeigen, dass die transkranielle SWE 1-2 Tage nach einem Schlaganfall zwischen Hirnhämatom und -infarkt unterscheiden kann [55]. Es besteht jedoch noch Bedarf an einer methodischen Standardisierung und an der Charakterisierung dynamischer Veränderungen der Gehirnelastizität [56].…”
Section: Wie Steht Es Um Den Transfer Neuerer Hirnultraschall-technol...unclassified
“…One study in neonates found an association between intraparenchymal hemorrhage and increased adjacent white and deep gray nuclei stiffness [ 52 ]. A study comparing ischemic and hemorrhagic stroke found increased stiffness within the region of infarct [ 60 ]. A separate rodent study investigating the effect of traumatic brain injury and hemorrhage on stiffness found the opposite, with brain injury and hemorrhage correlating with decreased stiffness at 24 h post injury [ 61 ].…”
Section: Elastographymentioning
confidence: 99%
“…The former study did not disclose the timeline between hemorrhage and elastography, and the disparity between the results may be related to the timing of injury. Elastography of the hemisphere contralateral to the intracranial pathology may provide information on degree of mass effect and midline shift [ 60 ]. Other changes, such as periventricular leukomalacia, may alter tissue stiffness in a manner detectable by elastography.…”
Section: Elastographymentioning
confidence: 99%
“…Shear wave elastography is useful for differentiating between benign and malignant tumors in the breast and brain [23,24]. In the brain, shear wave elastography can also be used to distinguish ischemic from hemorrhagic strokes [25]. In the kidney, shear wave elastography is employed to differentiate between mild-to-moderate and severe chronic changes [26].…”
Section: Introductionmentioning
confidence: 99%